Legalitas Penguasaan Tanah Pesisir Pantai oleh Orang Asing Dalam Bisnis Kepariwisataan, Desa Adat Canggu, Kecamatan Kuta Utara, Kabupaten Badung - Putu Ayu Sriasih Wesna; I Nyoman Sujana; I Wayan Kartika Jaya Utama (Universitas Warmadewa, 2023)
This Community Service is focused on socializing the legal legality of controlling coastal land by foreigners in Bali for tourism business purposes. The method used is empirical legal research with a statutory regulatory approach, conceptual approach, sociological approach and case approach. Based on authority theory, benefit theory and legal protection theory as analytical tools, it can be understood that the tourism business in Bali cannot be separated from the presence of foreigners. Likewise, the control of coastal land in Bali is not free from control by foreigners, either through legal or illegal investment, by taking advantage of mutually beneficial cooperation between local residents, as well as with Ada Village officials on the basis of sharing profits. The Balinese people, who have a unique culture with Hindu religious nuances, in their daily lives and in running business in the tourism sector are always based on the